Ta’ṡiru Wasā’ili al Bālūni li Mādati al Alwāni fī Ta’līmi al Lughati al ‘Arabiyyati bi Al Madrasati al Ṡānawiyyati al Islāmiyyati al Ḥukūmiyyati al Ṡāniyati bi Madīnati Jāmbī - Maharani, Krissella; Prihartini, Yogia (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
This study discusses the effect of balloon media on colorful material in learning Arabic at Madrasah Tsanawiyah Negeri 2 Jambi City. The purpose of this study was to prove that balloon media has a significant influence on students' understanding of colors in class VII at Madrasah Tsanawiyah Negeri 2 Jambi City. This research is a quantitative research by applying the experimental method, with a True Experimental Design type of Posttest-Only Control Design. The sample used in this study was 62 students in 2 classes. Sampling was carried out using probability sampling technique, which includes simple random sampling. Data collection techniques are carried out using observation, tests, and documentation. The results in this study indicate that understanding in learning colors after being given treatment obtained a higher score with an average value of 84.03 than before being given treatment with an average value of 59.52. Based on calculations using the Paired Samples t Test, the value of t = 12,517, df = 30 and Sig. (2-tailed) 0.000 ˃ 0.05. Thus the significant value is smaller than the error level or H0 is rejected and Ha is accepted.